1995
DOI: 10.1016/0029-7844(95)00286-z
|View full text |Cite
|
Sign up to set email alerts
|

Gynecologic history of women with inflammatory bowel disease

Abstract: Gynecologic conditions are common in women with inflammatory bowel disease, including menstrual abnormalities, vaginal discharge, infertility, and gynecologic surgery. All physicians providing care for women with inflammatory bowel disease should be familiar with the frequency and nature of concurrent gynecologic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…This study differs from previously published literature 5,9,10 in that it is broadly representative of IBD patients in the region, included both male and female patients, and involved a large number (and high proportion) of invited patients. The high response rate compared to other studies on this subject may be related to the vigorous follow-up of nonresponders.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…This study differs from previously published literature 5,9,10 in that it is broadly representative of IBD patients in the region, included both male and female patients, and involved a large number (and high proportion) of invited patients. The high response rate compared to other studies on this subject may be related to the vigorous follow-up of nonresponders.…”
Section: Discussionmentioning
confidence: 73%
“…The reasons for this may lie in the increase in ''mechanical'' sexual difficulties in women with IBD secondary to dyspareunia, lubrication problems, and vaginal discharge, 9 but other issues, such as fear of incontinence, are universal to men and women. Another reason for females to report an impact of IBD on these areas at a greater rate than men is the psychosocial differences between men and women with regard to selfimage and sociological factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been reported that the opioid concentration in peripheral mononuclear cells was reduced in the luteal phase in endometriosis patients compared with in controls (25), presumably because of opioid peptide release from neutrophils caused by IL-8 in peripheral blood. Our findings may also shed light on unexplained associations with ovarian dysfunctions and reduced fertility occurring mostly during the active stage of human inflammatory bowel disease (26)(27)(28), because in a rat model of severe colitis, a significant decrease in uterine neutrophils was reportedly associated with estrous cycle disturbance (26). Our findings therefore may provide a novel therapy for some forms of infertility involving normalization of the serum IL-8 level.…”
Section: Discussionmentioning
confidence: 87%
“…Weber et al examined 360 women with Crohn's disease (CD) and 251 women with ulcerative colitis (UC) who underwent surgery for their disease. 63,64 The reported menstrual abnormalities were oligomenorrhea, polymenorrhea, menorraghia, and metrorraghia. Compared with 53% of the women with UC, 60% of the women with CD reported an abnormality of the menstrual cycle.…”
Section: Gastrointestinal Conditionsmentioning
confidence: 98%